Modern Approaches and Methods for Assessing the Quality of Education - Khudaikulova Fazilat Bo‘rievna (International Journal of Formal Education, 2025)
This article discusses current issues related to the assessment of the quality of education, various approaches, methods and criteria in the research process . The article emphasizes approaches to the criteria for the quality of the results of the educational process, the criteria for the quality of the conditions for the implementation of the educational process, and the criteria for the quality of the implementation of the educational process.